Genetic variation and characterization of the sucrose synthase 2 gene (Sus2) in sugarcane based molecular markers - RINA SRI KASIAMDARI; DEA FEBIANSI; HERI PRABOWO; Ganies Riza Aristya; ARNI MUSTHOFA (Society for Indonesian Biodiversity, 2019)
Abstract. Kasiamdari RS, Febiansi D, Prabowo H, Aristya GR, Musthofa A. 2019. Genetic variation and characterization of the sucrose synthase 2 gene (Sus2) in sugarcane based molecular markers. Biodiversitas 20: 3087-3096. Sugarcane (Saccharum spp.) genotype is one of the sugar-producing plants and an important commodity to support the community’s economy. Plant breeders continuously cross-breed these plants to obtain cultivars with desirable traits to produce a variety of new phenotypes. An analysis of variation at gene-level is carried out as an important step in plant breeding programs. The purpose of the present study was to determine genetic variation and characterize the sucrose synthase 2 gene (Sus2) based on molecular markers. Twenty sugarcane cultivars were sampled from Indonesian Sweetener and Fiber Crops Research Institute (BALITTAS) Malang and four sugarcane cultivars from PT. Madu Baru in Polosio A Plantation, Poncosari, Srandakan, Bantul Regency, Yogyakarta. DNAs were amplified using two primer pairs, i.e. AI and SMC226CG. The genetic variations of the twenty-four sugarcane cultivars were analyzed by constructing a dendrogram of the Amplified DNA using Multi-Variate Statistical Package (MVSP) software. The results showed that there were three large clusters, namely Cluster A consisting of ‘PS 865’, ‘PS 951’, ‘PS 921’, and ‘PS 58’, with a similarity index of 57%; Cluster B consisting of the sugarcane ‘Kentung’, with a similarity index of 33%; and cluster C consisting of the sugarcane ‘PSDK 923’, ‘PSBM 901’, ‘TLH 2’, ‘BL’, ‘PSJT 941’, ‘KK’, ‘PS 80.1649’, ‘PSCO 902’, ‘PS 80,910’, ‘PS 882’, ‘PS 862’, ‘PS 851’, ‘PS 881’, ‘PS 865’, ‘PS 384’, ‘VMC 76-16’, ‘BZ 132’, ‘PS 891’, ‘PS 41’ with a similarity index of 60%. Polymorphisms occurred after the DNAs were amplified and after the bands appeared in heterozygous and homozygous individuals. In sugarcane, the Sus2 gene when detected by the molecular marker primer AI showed high-sucrose sugarcane; whereas the Sus2 gene detected by the primer SMC226CG showed low-sucrose sugarcane. Results of the present study showed that all sugarcane samples were detected as having low sucrose except Bulu Lawang and Kentung cultivars.